Association between body mass index and health-related quality of life among Chinese elderly—evidence from a community-based study - You, Hua; Li, Xiao-lu; Jing, Kang-zhen; Li, Zhi-guang; Cao, Hong-mei; Wang, Jin; Bai, Lan; Gu, Jing-hong; Fan, Xiaoman; Gu, Hai (BMC public health, 2018)
Background This study aimed to explore the effects of (body mass index) BMI on health related quality of life (HRQoL) among the elderly in Jiangsu, China. Methods A total of 10,257 community dwelling elderly (≥60 years old) were enrolled in a cross-sectional study. HRQoL was measured via the Eq-5d-3 L. Chi-square tests and one-way ANOVA analyses were used to compare the frequencies and scores of Eq-5d responses among different BMI groups (defined as “underweight”, “normal weight”, “overweight” and “obese”). Logistic regression analyses were conducted to examine the associations between BMI and HRQoL. Results Among the subjects, the proportion of “normal weight”, “underweight”, “overweight” and “obese” were 66.0, 8.3, 23.1, and 2.6%, respectively. The score of the Eq-5d index among total participants was 0.8036 and the Visual Analog Scale (VAS) score was 75.47. For both the responses frequency and scores of Eq-5d-3 L, there were significant differences among BMI groups ( P < 0.001). The Logistic regression model showed that both in men and women, underweight elderly were more likely to suffer low HRQoL. The adjusted odds ratio (OR) with a 95% confidence interval (CI) for Eq-5d index/VAS was 2.03 (1.48, 2.79)/1.83 (1.34, 2.50) in men and 1.47(1.09,1.98)/1.52(1.20,1.91) in women. Overweight women more likely to have a low Eq-5d index, while overweight men were less likely to have a low Eq-5d VAS. Conclusion This study shows that underweight is an explicit risk factor of low HRQoL in both the male and female elderly, while the effect of overweight on low HRQoL varies slightly by gender.